The Development of Hybrid Social Enterprises and Governance Management in Thailand - Wunsuk, Praphaphan (2022)
Social enterprises are hybrid organisations with social, environmental, and economic goals that combine business with traditional (for-profit) approaches and voluntary (non-profit) logics. They benefit society by carrying out community-based activities that enhance social, environmental, and economic values. Unfortunately, their ‘triple bottom line’ approach means they often experience difficulties, including conflict. While hybrid social enterprises deserve the attention of theoretical and empirical research, only a limited amount of empirical evidence is available that relates to such organisations and their governance. Despite having seen a significant rise in social enterprises over recent years, this situation is particularly true in Thailand. The proliferation of Thai social enterprises stemmed since the launch of the national Pracharath Rak Samakkee (PRS) social enterprise policy in 2015. PRS promoted a new social enterprise structure that enabled diverse sectors to work together under its guidance and governance framework. This research explores the features of hybrid social enterprises in Thailand, considers their positioning along the hybrid spectrum, and examines how they navigate the dilemmas, paradoxes and tensions associated with their development. The research utilises a qualitative research method using interviews, focus groups, document analysis, and observations. It included four case studies that took place in various parts of Thailand and the collection of empirical data during face-to-face interviews with forty-seven dominant stakeholders and two focus groups. The use of these case studies could be considered the first attempt at understanding the hybridity and governance of social enterprises established in Thailand based on the social enterprise national policy introduced in 2015. The findings reveal that government policy support, stakeholder involvement, solid practices (including business planning), resource support, and community readiness and capacity are facilitating factors in the formulation and development of social enterprises. With the same operational features as hybrid social enterprises, the case studies revealed that despite their benefits, the paradoxes of their ‘triple mission’ approach result in challenges in two key areas: balancing goals and conflicting interests. Understanding the research findings requires the consideration of a combination of stewardship and stakeholder theories. The research findings suggest employing the PRS social enterprise governance framework can mitigate the tensions inherent in the development of hybrid social enterprises. Likewise, developing competencies in areas like setting governance structure, prioritising and balancing missions, improving organisational performance, and utilising the social and market skills of expert board members were also shown to be beneficial, as was taking a highly collaborative approach to stakeholders in the governance process and empowering their actions. This mix of perspectives reflects the dominance of stewardship and stakeholder governance as they relate to the circumstances of the cases. This research benefits policymakers, academics, and practitioners by offering insight into the governance arrangements required to recognise and address tensions in multi-purpose organisations and across different stakeholders.